The expression and induction of heat shock proteins in molluscs - Liu, Dongwu; Chen, Zhiwei (Protein and peptide letters, 2013)
Living cells respond to stress stimuli by triggering rapid changes in the protein profiles, and the induction of heat shock proteins (HSPs) plays an important part in this process. HSPs, mainly acting as molecular chaperones, are constitutively expressed in cells and involved in protein folding, assembly, degradation, and intracellular localization. The overexpression of HSPs represents a ubiquitous molecular mechanism to cope with stress. Compared to vertebrates, molluscs have a biphasic life cycle where pelagic larvae go through settlement and metamorphosis. HSPs may play an important role in the survival strategy of molluscs during the biphasic life stages. Since aquatic environments are highly dynamic, molluscs may be subject to a variety of sources of stress and HSPs might play a more important role in the adaptation of these animals. Moreover, the mechanisms of stress tolerance in molluscs can offer fundamental insights into the adaptation of organisms for a wide range of environmental challenges. The cDNA of HSPs has been cloned from some molluscs, and HSPs can be induced by heat stress, hypoxia, heavy metal contamination, and aestivation, etc. The expression of HSPs was detected in the neuroendocrine system, mollusc development, and reproductive process. Furthermore, the induction of HSPs is related with the phosphorylation of stress-activated p38 mitogen-activated protein kinase (p38 MAPK) and cJun-N-terminal kinases (JNKs) in molluscs.